Comparison of renal stiffness between diabetic patients and healthy controls using shear wave elastography - Wang, Zifan (2022)
Type Ⅱ diabetes Mellitus（T2DM）is a relatively common chronic disease. The most common complication of T2DM is diabetic kidney disease (DKD). This complication has a high mortality rate, and patients have a poor prognosis and health status. Therefore, diagnosis and treatment at an early stage of DKD are particularly important. The most common clinical screening methods for kidney disease are computed tomography (CT), ultrasound (US), magnetic resonance imaging (MRI), and biochemical studies. However, these methods are not specific for early detection of DKD disease. According to diabetes guidelines, the gold standard for chronic kidney disease (CKD) is tissue biopsy. This is an invasive and expensive test that is rarely used in clinical practice. The prognosis and survival of patients with DKD have become a public health issue. Early detection of the onset of DKD and timely treatment can help patients improve their prognosis and quality of life. The Second Affiliated Hospital of XinXiang Medical University was used to recruit 62 volunteers for this study. Based on their glucose metabolism, they were divided into 3 groups: Normal Glucose Metabolism (NGM), Pre-Diabetes Mellitus (Pre- DM) and T2DM. Each patient's medical history, baseline demographic data, laboratory data, and ultrasound data were systematically recorded. Renal cortical stiffness (CS) values were measured by shear wave elastography (SWE) technique of conventional 2D ultrasound. The three sets of data obtained in the experiment were compared to clarify differences between and within groups. Possible early signs of DKD were detected and identified by examining the functional curve characteristics of the participants. With the exception of heart rate and blood pressure, all demographic data were identical in the three groups. When laboratory data were analyzed, all laboratory values differed between the groups, with the exception of uric acid. Blood glucose, lipid, and blood urea nitrogen levels were significantly higher in T2DM than in the other groups. Pre- DM and T2DM had higher LDL, creatinine, and microalbumin than NGM. In US examinations, all ultrasound parameters were the same in Pre- DM and T2DM. Kidney length, kidney width, and cortical stiffness were higher in pre- DM and T2DM than in the NGM group. The CS value of patients with abnormal glucose metabolism was higher than that of NGM. Renal length and cortical thickness were independently correlated with renal stiffness (r = 0.335 and r = 0.411, respectively). Kidney thickness was an independent determinant of CS level. In the ROC analysis, with a renal CS level of 8.5 Kpa, the specificity and sensitivity of CS for predicting the occurrence of nephropathy were 66.7% and 66.9%, respectively. The CS values of subjects with impaired glucose metabolism were significantly higher in this study based on their glucose metabolism. The performance of the SWE as a non-invasive tool for diagnosing DKD is better than traditional examination, and it is expected to detect and diagnose DKD early. CS Values assessed by SWE should be used as a standard test for screening early nephropathy in Pre-DM and newly diagnosed T2DM. According to the results, it should be widely used in medical care.